Diversification of Lifelong Learning at Taman Pendidikan Al-Qur’an (TPQ) Al-Muttaqin and the Surrounding Community - Wiyanti; Khadijah Dzikrullah; Aviena Sabila (CV. Kayaswara, 2025)
Lifelong religious education is an urgent need in modern society that is experiencing spiritual and social challenges. This study aims to analyze the contribution of program management implemented at TPQ Al-Muttaqiin in expanding access to Islamic education for all ages in society. With a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, documentation, and literature studies of various scientific sources. The results of the study indicate that TPQ Al-Muttaqiin implements program management based on community needs through diversification of activities, such as Iqra’ classes, adult tahsin, fiqh studies, adzan training, Islamic literacy, and sharia UMKM training. Planning is carried out in a participatory manner with community leaders and guardians of students, while evaluations are carried out periodically and based on feedback. The findings show that there has been a significant social transformation, both in increasing individual religiosity, parental involvement, strengthening social relationships, and economic empowerment based on Islamic values. In conclusion, TPQ Al-Muttaqiin has succeeded in becoming a model of a responsive, inclusive, and transformative non-formal Islamic educational institution by integrating spiritual and social values ​​within the framework of lifelong education. Adaptive management that is implemented makes TPQ a center for relevant and sustainable Qur’anic learning in the midst of urban society.